Kontribusi Kemenarikan Interpersonal Konselor pada Motivasi Siswa dalam Mengikuti Bimbingan Kelompok di Kota Malang - Hanggara, Guruh Sukma; Putri, Nora Yuniar Setya (Psikopedagogia, 2017)
This study aimed to find out the relationship between the counselor’ interpersonal attractiveness and the students' motivation in participating the group guidance. This was a correlational study. The subject of this study was 246 students of the eleventh grade of state senior high schools in Malang city as the respondents. The subject of this study was taken by cluster random sampling technique. This study employed Pearson product-moment correlational test to analyze the data.  The result of this study showed a positive and significant relationship between the counselor’ interpersonal attractiveness and state senior high school students’ motivation in participating group guidance by (r = 0.622) and (p= 0.000 < 0.05). Higher counselor’ interpersonal attractiveness leads to higher students’ motivation in participating group guidance. This study proved the importance of the counselor’ interpersonal attractiveness in providing group guidance so that the students are highly motivated to participate in group guidance service.